Akibat Hukum Terjadinya Subrogasi Objek Waris dalam Sengketa Waris Perdata - Radius Prayogo; Benny Djaja (LPPM Universitas Ekasakti Padang, 2023)
Indonesian civil code generally regulates inheritance rights between blood relatives which in fact aanvullen recht (openness). Openness here means that they are not required to follow what has been regulated or in other words each and every heir is entitled to the inheritance as long as they are tolerant to the results of the distribution portion and they are contend with it. However, the problem arises when there is one or more heirs who start a dispute which ultimately resulted and processed in court. Even more so complicated when the inheritance object had previously been mortgaged to the Bank. The form of debt repayment that occurred on the collateral could significantly affect the inheritance, especially when subrogation happened. The legal consequences focus on whoever holds the subrogative rights and as such gets preferential rights in the distribution of the inheritance.